Comparison of Value System among a Group of Military Prisoners with Controls in Tehran. - Seyed Mahmood Mirzamani (Iranian Journal of Psychiatry, 2011)
Religious values were investigated in a group of Iranian Revolutionary Guards in Tehran.The sample consisted of official duty troops and conscripts who were in prison due to a crime. One hundred thirty seven individuals cooperated with us in the project (37 Official personnel and 100 conscripts). The instruments used included a demographic questionnaire containing personal data and the Allport, Vernon and Lindzey's Study of Values Test. Most statistical methods used descriptive statistical methods such as frequency, mean, tables and t-test.The results showed that religious value was lower in the criminal group than the control group (p